Adult Hippocampal Neurogenesis Modulation by the Membrane-Associated Progesterone Receptor Family Member Neudesin - Novais, Ashley; Silva, Alberto; Ferreira, Ana Catarina; Falcão, Ana Mendanha; Sousa, Nuno; Palha, Joana Almeida; Marques, Fernanda; Sousa, João Carlos (Frontiers in Cellular Neuroscience, 2018)
Neudesin (NENF), a membrane-associated progesterone receptor family (MAPR) member, is a neuron secreted protein with neurotrophic properties during embryonic stages. However, its role in the adult brain is still poorly addressed. In this study we have used neudesin-null (Nenf-/-) mice and performed a characterization of the proliferation state of the adult neurogenic niches, the adult subventricular zone (SVZ) and the hippocampus subgranular zone (SGZ). Nenf-/- males did not presented any deficits in proliferation in the SVZ neither in vivo nor in vitro. On the other hand a decrease in cell proliferation in the SGZ was observed, as well as a decrease in the number of newborn neurons in the dentate gyrus (DG) that was accompanied by impaired context discrimination in a contextual fear conditioning task. Since NENF neurotrophic action is suggested to occur via the formation of a progesterone stability complex for the activation of non-genomic cascade, we further evaluated progesterone metabolism in the absence of NENF. Interestingly, expression of progesterone catabolic rate-determining enzyme, 5-α-reductase was upregulated in the DG of Nenf-/-, together with a significant increase in the expression of the δGABAA receptor gene, involved in DG tonic inhibition. Taken together, these findings add in vivo evidence on the neurotrophic properties of NENF in the adult brain. Furthermore, the mechanism of action of NENF in this process might implicate neurosteroids modulation, at least in the DG.